Topical axitinib suppresses angiogenesis pathways induced by pulsed dye laser. (11th December 2014) - Gao, L.; Nadora, D.M.; Phan, S.; Chernova, M.; Sun, V.; Preciado, S.M.O.; Jia, W.; Wang, G.; Mihm, M.C.; Nelson, J.S.; Tan, W.
Summary: Background: The recurrence of port‐wine stain (PWS) blood vessels by pulsed dye laser (PDL)‐induced angiogenesis is a critical barrier that must be overcome to achieve a better therapeutic outcome. Objectives: To determine whether PDL‐induced angiogenesis can be suppressed by topical axitinib. Methods: The mRNA expression profiles of 86 angiogenic genes and phosphorylation levels of extracellular signal regulated kinases (ERKs), phosphorylated protein kinase B (AKT) and ribosomal protein S6 kinase (p70S6K) in rodent skin were examined with or without topical axitinib administration after PDL exposure. Results: The PDL‐induced increased transcriptional levels of angiogenic genes peaked at days 3–7 post‐PDL exposure. Topical application of 0·5% axitinib effectively suppressed the PDL‐induced increase in mRNA levels of the examined angiogenic genes and activation of AKT, P70S6K and ERK from days 1 to 7 post‐PDL exposure. After topical administration, axitinib penetrated into rodent skin to an approximate depth of 929·5 μm. Conclusions: Topical application of 0·5% axitinib can systematically suppress the PDL‐induced early stages of angiogenesis via inhibition of the AKT/mammalian target of rapamycin/p70S6K and Src homology 2 domain containing transforming protein‐1/mitogen‐activated protein kinase kinase/ERK pathway cascades. Abstract : What's already known about this topic? The regeneration of blood vessels in port‐wine stain (PWS) after pulsed dye laser treatment is a critical barrier that must be overcome to achieve an adequate therapeutic outcome. Activation of angiogenesis pathways induced by PDL contributes to PWS blood vessel recurrence. What does this study add? Topical application of 0·5% axitinib can systematically suppress PDL‐induced angiogenesis. We propose a potentially new therapeutic strategy using PDL + axitinib for the clinical management of patients with PWS.